Strategy Public Affairs Programs: CSR Wash Aqua Golden Mississippi Sukabumi - Hilda Sri Rahayu; Umban Adi Jaya (Jurnal Audiens, 2024)
In Indonesia, Corporate Social Responsibility (CSR) faces challenges in public affairs and is connected to companies' efforts to create a good public image through CSR Programmes. This study focuses on PT Aqua Golden Mississippi Mekarsari's CSR programme and the Public Affairs strategies used by the CSR department. The study was conducted in the CSR Department of PT Aqua Golden Mississippi. It specifically examines the public affairs strategies related to the WASH CSR programme. The research analyzes the public affairs strategy implemented by the CSR Department of PT Aqua Golden Mississippi Mekarsari towards the community of Benda Village, Cicurug Subdistrict. The stakeholders involved in the Wash CSR program include NGOs, Government, and Media. The research used a qualitative method with a case study approach. The findings reveal that PT Aqua Golden Mississippi Mekarsari collaborates with stakeholders such as NGOs, Government, and media to overcome resistance to the CSR program. In conclusion, while CSR programmes aim to create a positive public opinion, community resistance may not significantly impact CSR initiatives. Therefore, it is crucial to thoroughly identify, analyze, and implement well-evaluated strategies to ensure the success of CSR programmes.